Body piercing and tattoos: a survey on young adults' knowledge of the risks and practices in body art - Caggiano Giuseppina; Montagna Claudio; Fasano Fabrizio; Napoli Christian; Quaranta Alessia; Montagna Maria (BMC, 2011)
Abstract Background The practice of tattooing and piercing has expanded in western society. In order to verify young adults' knowledge of the risk and practices related to body art, an investigation was conducted among freshmen of the University of Bari in the region of Apulia, Italy. Methods The study was carried out in the Academic Year 2009-2010 through an anonymous self-administered written questionnaire distributed to 1.656 freshmen enrolled in 17 Degree Courses. Results Of the 1.598 students included in the analysis, 78.3% believe it is risky to undergo piercing/tattoo practices. AIDS was indicated as a possible infection by 60.3% of freshmen, hepatitis C by 38.2%, tetanus by 34.3% and hepatitis B by 33.7% of the sample. 28.1% of freshmen were not aware that there are also non-infectious complications. 29% of the sample had at least one piercing or tattoo (this percentage does not include earlobe piercing in women). Of those with body art, the decision to undergo body art was made autonomously in 57.9% of the participants. 56.3% of freshmen undergoing body art had taken less than a month to decide. With regard to the reasons that led the sample to undergo body art, 28.4% were unable to explain it, 23.8% answered to improve their aesthetic aspect, 18.4% to distinguish themselves from others, 12.3% for fashion; 17.1% for other reasons. 25.4% of the sample declared that they had a piercing (79.8% female vs 20.2% male; ratio M/F 1:4.0). The average age for a first piercing was 15.3 years (range 10-27; SD ± 2.9). 9.6% of the sample declared that they have a tattoo (69.9% female vs 30.1% male; ratio M/F 1:2.3). The average age for a first tattoo was 17.5 years (range 10-26, SD ± 2.4). Conclusions Most of the freshmen knew about AIDS-related risks but not other potential risks. Body art is fairly common among young adults (especially women). The decision is often not shared with the family and is undertaken mostly without a specific reason or for the improvement of aesthetic aspect. Information about freshmen's knowledge, attitudes and practices could help in effective planning of health promotion strategies.